2018
DOI: 10.1007/s13178-018-0343-z
|View full text |Cite
|
Sign up to set email alerts
|

Cohabitation and Romantic Relationship Quality Among Portuguese Lesbian, Gay, and Heterosexual Individuals

Abstract: Sexuality Research and Social Policy. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…In a more recent study, findings pointed toward LGBTQ+ couples experiencing higher levels of relationship satisfaction and fulfilment and lower levels of conflict with their partners (Lampis et al, 2021, p. 50). Rodrigues (2019) hypothesizes that Research has shown that same-sex and different-sex relationships do not differ in their quality or functioning (e.g., satisfaction, love, intimacy), presumably because individuals are guided by similar principles when developing voluntary and significant relationships, regardless of their sexual orientation. (p. 100) One of the main factors that will lead to decreased satisfaction in both LGBTQ+ and heterosexual relationships is the presence of stereotypical gender roles (Lampis et al, 2021, p. 50).…”
Section: Lgbtq+ Versus Heterosexual Relationshipsmentioning
confidence: 99%
“…In a more recent study, findings pointed toward LGBTQ+ couples experiencing higher levels of relationship satisfaction and fulfilment and lower levels of conflict with their partners (Lampis et al, 2021, p. 50). Rodrigues (2019) hypothesizes that Research has shown that same-sex and different-sex relationships do not differ in their quality or functioning (e.g., satisfaction, love, intimacy), presumably because individuals are guided by similar principles when developing voluntary and significant relationships, regardless of their sexual orientation. (p. 100) One of the main factors that will lead to decreased satisfaction in both LGBTQ+ and heterosexual relationships is the presence of stereotypical gender roles (Lampis et al, 2021, p. 50).…”
Section: Lgbtq+ Versus Heterosexual Relationshipsmentioning
confidence: 99%
“…For example, women in abusive relationships who lack quality alternatives and have a lot invested with that partner may decide to stay in that relationship even if they are not satisfied with the relationship (Rusbult & Martz, 1995). Prior studies (e.g., Mattingly, Wilson, Clark, Bequette, & Weidler, 2010;Rodrigues, Lopes, & Prada, 2019;Strelan & Pagoudis, 2018) have used these investment model constructs to examine relationship quality.…”
Section: The Investment Modelmentioning
confidence: 99%
“…Cohabitation has been shown as an important marker of relationship stability, as LG individuals perceive it as a symbol for how motivated both partners are to maintaining their relationship (Haas & Whitton, 2015). Research showed that cohabiting LG individuals report overall similar relationship quality, regardless of whether their union is legally recognized or not (Rodrigues et al, 2018). By cohabiting, individuals are able to spend more time together and create mutual emotional support, which helps ascribe greater meaning and intimacy to the relationship (Reczek, Elliott, & Umberson, 2009; Rostosky, Riggle, Dudley, & Wright, 2006), and create a sense of family (Haas & Whitton, 2015).…”
Section: Cohabitation In Same-sex Relationshipsmentioning
confidence: 99%
“…They are also better at reframing both negative social contexts and experienced stigmatization into opportunities to bond with their partner (Connolloy, 2006), which strengthens relationship closeness (Frost, 2011, 2014; Rostosky et al, 2007). Importantly, whereas some of the studies examining the role of cohabitation and social support in same-sex relationships do not examine gender differences (e.g., Holmberg & Blair, 2016; Rodrigues et al, 2018), others report inconsistent findings regarding the association between perceived social support and relationship quality (Lavner, 2017).…”
Section: Social Support In Same-sex Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation